Demineralized dentin matrix promotes gingival healing in alveolar ridge preservation of premolars extracted for orthodontic reason: a split-mouth study - Xu, Xiaofeng; Peng, Dongsheng; Zhou, Bowei; Lin, Kaijin; Wang, Siyi; Zhao, Wei; Zheng, Minqian; Yang, Jin; Guo, Jianbin (Frontiers in Endocrinology, 2023)
The purpose of this study was to prospectively evaluate the efficacy of a demineralized dentin matrix (DDM) in decreasing the initial inflammatory response of the gingiva and facilitating the repair and regeneration of soft tissue in alveolar ridge preservation.: This clinical study employed a split-mouth design. Fourteen patients with a total of forty-four sites underwent extraction and alveolar ridge preservation (ARP) procedures. A Bilaterally symmetrical extraction operation was were conducted on the premolars of each patient. The experimental group received DDM as a graft material for ARP, while the control group underwent natural healing. Within the first month postoperatively, the pain condition, color, and swelling status of the extraction sites were initially assessed at different time pointsWithin the first month postoperatively, at different time points, the pain condition, color, and swelling status of the extraction sites were initially assessed. Subsequently, measurements were taken for buccal gingival margin height, buccal-lingual width, extraction socket contour, and the extraction socket area and healing rate were digitally measured. Additionally, Alcian Blue staining was used for histological evaluation of the content during alveolar socket healing.Results: Both groups experienced uneventful healing, with no adverse reactions observed at any of the extraction sites. The differences in VAS pain scores between the two groups postoperatively were not statistically significant. In the early stage of gingival tissue healing (3 days postoperatively), there were statistically significant differences in gingival condition and buccal gingival margin height between the two groups. In the later stage of gingival tissue healing (7, 14, and 30 days postoperatively), there were statistically significant differences in buccal-lingual width, extraction socket healing area, and healing rate between the two groups. Furthermore, the histological results from Alcian Blue staining suggested that the experimental group may play a significant role in promoting gingival tissue healing, possibly by regulating inflammatory responses when compared to the control group.The application of DDM in alveolar ridge preservation has been found to diminish initial gingival inflammation after tooth extraction. Additionally, it has shown the ability to accelerate early gingival soft tissue healing and preserve its anatomical contour.